Career Planning and Soft Skills - D, Swamy (IJRDO -Journal of Computer Science Engineering, 2016)
An attempt has been made in this paper to describe the details about competitiveexaminations and the following personality test including personal interview covering thecriteria used. The Career planning is the first step the candidates have to do. Different waysof collecting career information include reading, talking and job shadowing. Strengtheningreading comprehension is an important step in the process of preparing for examination. Anattempt has been made to list the steps for this process. Communication skills both writtenand oral play a vital role in the process of selection. The author gives a detailed account ofdifferent types of communication skills and stresses the need for developing confidence byadequate preparation, knowledge of examination pattern and adoption good study processare important steps for success.